STRATEGI PENCEGAHAN TINDAKAN TOXIC CULTURE DALAM PLATFORM GAME ONLINE DENGAN PENDEKATAN SOCIAL PREVENTION CRIME. - Salsa Septiana Jasmin; Anton Budi Saputra; Syahad Anugrah; Muhammad Akbar Aidino Setiawan Notobuono; Muhammad Faturrohman; Adilia Harika Putri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This article discusses the perspective of one of the approaches to crime prevention strategies, namely Social Prevention Crime in the case of Toxic Culture in online gaming platforms. The theory used in this study is to use the theory of social learning as evidenced by a person doing a Toxic Culture action because there are several factors such as encouragement, motivation, imitation, and the environment of family and friends. This article uses data collection techniques by means of literature studies or by the use of related documents. The results of this study indicate that the social crime Prevention approach can be done by education and counseling on the importance of good communication, as well as monitoring and moderation in online gaming platforms. In this way, it is possible to reduce Toxic Culture in online games.